Development and Evaluation of Articulate Storyline-Based Interactive Media: Integration of Socio-Scientific Issues in Hydrocarbon Learning to Enhance Students’ Critical Thinking Skills - Miranda Nora'in; Arif Sholahuddin; Norsifa Humaira; Febry Rosita; Siti Khadijah; Muhammad Ismi Rezani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Critical thinking enables students to make informed decisions, resist misinformation, and construct deeper disciplinary understanding, yet it remains underdeveloped in many classrooms. This study developed and evaluated an interactive hydrocarbon learning medium created with Articulate Storyline and integrating socioscientific issues (SSI) within the ADDIE framework (Analysis, Design, Development, Implementation, Evaluation). The research was conducted at an Islamic boarding school in Banjarmasin with 61 students (individual try-outs: n = 5; small-group trials: n = 10). Instruments—questionnaires, observation sheets, and tests—were aligned to Facione’s six critical-thinking indicators and used to assess validity, practicality, and effectiveness. Content and media validity were high (expert ratings: 0.89 and 0.88), internal consistency was acceptable (Cronbach’s alpha = 0.86), and practicality was rated very good (mean = 4.59). Effectiveness analyses showed substantial learning gains (normalized gain, n-gain = 0.77 and 0.78) and statistically significant pre- to post-improvements (paired t-tests, p < 0.001), indicating the medium effectively enhances students’ critical thinking in chemistry. Limitations include the focus on a single topic (hydrocarbons), a single site with a modest sample, and no assessment of other skills or long-term retention. Within these bounds, the media demonstrate strong quality and practical classroom value, supporting teachers to design engaging, student-centered instruction that cultivates deeper thinking.